Experimental validation of performance and degradation study of canal-top photovoltaic system - Kumar, Manish; Kumar, Arun (Applied energy, 2019)
•The performance analysis of utility-scale canal-top PV system has been carried out.•Experimental results show the low performance of PV module on the water surface.•High degradation rate has been found in the present 10 MWp canal-top PV system.•Shunt resistance degradation of PV module has been observed on the water surface.•Evaporation reduction by PV cover on the water surface is found to be 29.1%. The canal-top PV systems have different environmental conditions than the land-based system which may affect its performance and degradation rate. The performance and reliability of PV modules on the canal and reservoir are critical for ensuring the long lifetime, improvement and economic viability of the canal-top PV systems. The long-term performance analysis of the canal-top PV systems and their comparison with conventional land-based PV systems is not reported widely. The objective of the present study is to assess the suitability of PV systems on the canals for their large scale installations and reliable operation. In order to understand the long-term performance behavior of the PV systems on the canals, the performance and degradation analysis of world’s first commercial multicrystallinesilicon (Multi-Si) based 10 MWp canal-top PV system installed in the Indian state of Gujarat has been carried out for their initial 2 years 8 months operation. An experimental setup was fabricated to compare the performance of canal-top PV systems with the conventional land-based PV systems and measurements were carried out in the outdoor conditions for six months in the outdoor laboratory of Indian Institute of Technology Roorkee, India. To achieve a better understanding of the performance and degradation of PV modules, a single-diode PV model was developed to characterize the PV modules. Furthermore, the evaporation loss reduction by canal-top PV systems has not been reported widely and has been experimentally quantified under this study. The annual average performance ratio and degradation rate of 10 MWp canal-top PV system are found to be 77.85% and 1.93 ± 0.28%/year, respectively. Experimental comparison of water tank-based PV module and land-based PV module shows that the average performance ratio of Multi-Si module on the water surface is about 1.5% lower compared to land-based Multi-Si module which is contrary to the general perception of higher power production by the Multi-Si PV systems on the canals.